Preliminary Development of an Acid-Base Student Worksheet Based on Guided Discovery Learning Integrated with Ethnoscience to Foster Phase F Students' Critical Thinking Skills - Putri Ramadani; Nofri Yuhelman (SEARCH: Science Education Research Journal, 2026)
Students' difficulties in understanding acid-base concepts and the limited use of teaching materials that facilitate concept discovery and critical thinking indicate the need for more contextual learning resources. This study aimed to develop a preliminary prototype of an acid-base student worksheet (LKPD) based on Guided Discovery Learning integrated with ethnoscience, designed by incorporating Ennis's critical thinking indicators for Phase F students. The study employed Educational Design Research (EDR) using the Plomp development model and was limited to the preliminary research and prototyping phases. The participants consisted of four chemistry teachers and 60 Phase F students from SMAN 2 Pariaman, SMAN 4 Pariaman, and SMAN 2 Sungai Limau. Data were collected through interviews, questionnaires, literature review, and self-evaluation using interview guidelines, student needs questionnaires, and a self-evaluation checklist. The development process resulted in Prototype II following revisions to Prototype I based on the findings of the self-evaluation. Prototype II integrates Guided Discovery Learning syntax, Minangkabau ethnoscience contexts, and Ennis's critical thinking indicators as the basis for designing systematic learning activities. The resulting Prototype II represents the outcome of the preliminary development phase and is ready for expert validation as the next stage of the development process.